ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KOPI PADA WARKOP ON MADA RANTAUPRAPAT - Sinaga Simanjorang, Elida Florentina (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
This study aims to determine the effect of brand image, price and product quality factors on coffee purchasing decisions at Warkop On Mada Rantauprapat. The data collection methods used were questionnaires, interviews and observations. The population of this research is the consumers of Warkop On Mada Aek Tapa Rantauprapat. Because the population in this study is unknown, the sample determination uses the formula according to Wibisono. The data analysis technique used is multiple linear regression and hypothesis testing using the t-test to test the partial regression coefficient and the F test to test simultaneously. From this study, the regression equation Y = 6.229 + 0.195X1 + 0.207X2 + 0.253X3 + e is obtained. The results of this study indicate that the variables brand image, price and product quality both partially and simultaneously have a positive and significant effect on coffee purchasing decisions. Judging from the results of the determination coefficient test (R2) shows the magnitude of the contribution of the influence of the independent variables on the dependent variable, the results show the value of R2 = 0.302 which means that 30.2% of coffee purchasing decisions are influenced by brand image, price and product quality, while the rest is equal to 69.8% is influenced by other variables not studied.